Strategic Planning of the Location of PLN's Public Electric Vehicle Charging Station (SPKLU) in Bekasi City Based on Multi-Criteria Analysis - Sinatra, Donna; Suparno, Suparno (Riviera Publishing, 2026)
This study aims to determine the strategic locations for Public Electric Vehicle Charging Stations (SPKLU) in Bekasi City using a multi-criteria approach based on AHP–TOPSIS and financial feasibility evaluation through Cost–Benefit Analysis (CBA). The Analytic Hierarchy Process (AHP) was employed to establish criteria weights, including electric vehicle (EV) density, accessibility, energy infrastructure readiness, socio-economic factors, inter-station distance, and environmental aspects. Subsequently, TOPSIS was applied to assess the closeness of alternative locations to the ideal solution, while CBA was used to evaluate the economic viability of the project. The results indicate that the most influential criteria are EV density, accessibility, and energy infrastructure readiness. Mall Sumarecon Bekasi achieved the highest preference score (Ci = 1.0), designating it as the primary priority for SPKLU development. The City Hall and Islamic Center ranked second and third, respectively, serving as secondary locations to expand service coverage and support network stability. CBA analysis shows that Mall Sumarecon has a Benefit–Cost Ratio (BCR) of 0.98, approaching the financial feasibility threshold, with additional social benefits including carbon emission reduction and improved air quality. Based on these findings, it is recommended to prioritize SPKLU construction at Mall Sumarecon, develop the City Hall and Islamic Center as secondary locations, and implement monitoring, integration of socio-environmental factors, long-term planning, and public education. This study emphasizes the importance of a holistic approach in SPKLU location planning to support mobility, sustainability, and equitable access to electric transportation in Bekasi City.